QUALITATIVE ANALYSIS OF SAPONINS IN THE COMPOSITION OF Allium suworowii PLANT (Scientific journal of the Fergana State University, 2026)
The article examines the qualitative analysis of saponins found in the plant Allium suworowii. The study investigates the chemical composition of the saponins extracted from the plant and their properties. The main components of the saponins are identified, and their characteristics — including their natural forms and structure — are analyzed. The results of the analysis reveal the qualitative significance of the saponins present in the plant.